Adolescents and adults with FOXP1 syndrome show high rates of anxiety and externalizing behaviors but not psychiatric decompensation or skill loss - Levy, Tess; Silver, Hailey; Soufer, Renee; Rouhandeh, Audrey; Kolevzon, Alexander; Buxbaum, Joseph D.; Siper, Paige M. (Frontiers in Psychiatry, 2025)
BackgroundFOXP1 syndrome is a genetic neurodevelopmental disorder associated with complex clinical presentations including global developmental delay, mild to profound intellectual disability, speech and language impairment, autism traits, attention-deficit/hyperactivity disorder (ADHD), and a range of behavioral challenges. To date, much of the literature focuses on childhood symptoms and little is known about the FOXP1 syndrome phenotype in adolescence or adulthood.MethodsA series of caregiver interviews and standardized questionnaires assessed psychiatric and behavioral features of 20 adolescents and adults with FOXP1 syndrome. Clinical interviews captured change in various psychiatric manifestations over time. Medication, social, educational, and vocational history was collected, and visual analog scales measured top caregiver concerns during childhood and adolescence/adulthood.ResultsAnxiety and externalizing behaviors were common in this cohort and psychiatric features, such as psychosis or bipolar symptoms, were present in two participants. There was no reported regression or loss of skills, early in development or during adolescence/adulthood. Medication use was common particularly for features of ADHD, although multiple trials were required for some individuals to achieve benefit. Standardized assessments accurately picked up on externalizing symptoms and were less sensitive to internalizing symptoms. Educational setting varied up until late elementary school and gradually shifted to special education. Cognitive and developmental concerns were reported as primary during childhood and independence/safety and housing concerns became top concerns by adolescence/adulthood. Caregivers reported continued development in adaptive skills even into adulthood.ConclusionsTaken together, results are reassuring, with many families reporting their adolescent and adult children continued to gain skills over time, particularly related to increased independence in communication and personal care. There were no reports of developmental regression, neuropsychiatric decompensation or catatonia.